Health-Related Quality of Life in Patients With Hodgkin Lymphoma: A Longitudinal Analysis of the German Hodgkin Study Group - Kreissl, Stefanie; Müller, Horst; Goergen, Helen; Meissner, Julia; Topp, Max; Sökler, Martin; Markova, Jana; Bernhard, Jürg; Greil, Richard; von Tresckow, Bastian; Behringer, Karolin; Rüffer, Jens-Ulrich; et al. (Journal of clinical oncology, 2020)
PURPOSE: Many important details of health-related quality of life (HRQoL) after diagnosis and treatment of Hodgkin lymphoma (HL) are still unknown because large longitudinal studies of HRQoL are rare. Therefore, we analyzed a systematically assessed, comprehensive range of HRQoL domains in patients with HL of all stages from diagnosis up to 5 years of survivorship. PATIENTS AND METHODS: We included patients with HL age 18-60 years at diagnosis from the German Hodgkin Study Group trials HD13, HD14, and HD15. We analyzed HRQoL using all functional and symptom scales of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 including deviations from reference values. We estimated the effect of different disease, patient, and treatment characteristics using multiple regression and repeated measures analysis and computed correlations of HRQoL scores. RESULTS: We analyzed 4,215 patients with any HRQoL assessment within 5 years after treatment. Higher tumor burden at diagnosis was associated with impaired baseline scores in many HRQoL domains. During survivorship, cognitive, emotional, role, and social functioning and fatigue, dyspnea, sleep, and financial problems were severely and persistently affected. From year 2 on, mean deviations from reference values ranged between 12 and 29 points, with 10 points being a commonly used margin of clinical relevance. In all 3 trials, HRQoL domains 2 and 5 years after therapy were significantly influenced by baseline scores and age but not by randomized treatments. Fatigue was most closely correlated with other symptoms and scales. CONCLUSION: Our results show a high and persistent amount of different HRQoL deficits in survivors of HL that are largely independent of the applied chemotherapies. Our analysis underscores the high, unmet medical need of these rather young survivors of HL regarding the psychosocial adverse effects of the cancer experience.
Keywords: Young Adult; Male; kvalita života; longitudinální studie; Quality of Life; mladý dospělý; Adolescent; Cancer Survivors; Adult; dospělí; mužské pohlaví; mladiství; Hodgkin Disease; Germany; lidé; ženské pohlaví; Humans; Německo; Hodgkinova nemoc; Longitudinal Studies; přežívající onkologičtí pacienti; Female; lidé středního věku; Middle Aged